2023 IFPRI annual report - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
IFPRI’s 2023 Annual Report offers highlights from our research around the world and of our analysis and communications on addressing global challenges that contribute to hunger and malnutrition. In 2023, IFPRI continued the critical work on crisis and resilience-building that began with the COVID-19 pandemic, the Russia-Ukraine war, and rising food prices. Our research also continued to inform policymakers and stakeholders on climate resilience and sustainability, healthy diets and nutrition, inclusive and efficient food systems, institutions and governance, and rural transformation, all with attention to gender and the world’s most vulnerable people, with the goals of reducing poverty and ending hunger and malnutrition.